English for academic purposes in the framework of the European Space of Higher Education: An example of teaching teams at Universidad Politécnica de Cartagena (UPCT) - Natalia CARBAJOSA (Ediciones Universidad de Salamanca, 2012)
The aim of this article is to introduce a case study carried out by a multidisciplinary teaching team who has studied, at the UPCT, the mechanisms for a progressive implementation of academic English in its schools, with the final purpose of achieving a bilingual teaching model. In a first theoretical stage, we explain how the teaching team focuses on the available concepts and theories concerned with languages for specific purposes, together with Bologna's guidelines about English as a transversal competence in all Higher Education institutions. Likewise, the team revises the level of implementation of academic bilingual programs in our surrounding countries. Later, the article describes the elaboration process of several materials by the teaching team, in which all the faculty of the UPCT has been involved. Such materials have finally led to the design of a training course for those lecturers who have introduced or are going to introduce English, partly or wholly, in the content subjects of their respective degrees, thus contributing to strengthening the presence of languages for specific purposes in our academic environment.